Estimation of Peoples' Perception on Climate Change Effect on Agriculture: A Participatory and Socio-personal Analysis - Jena, A; Acharya, S K (Indian Journal of Extension Education, 2016)
Climate change has been recognized globally as an ever increasing threat. The economic and social implications of global  climate change are the subject of intense national and international study in present day scenario. The present study has  delved deeper into the peoples' perception on congenital effect of climate change on agriculture in regards to coastal agro ecosystem of Odisha. The study has been based on a blend between participatory rural appraisal and a conventional  multivariate statistical analysis including correlation coefficient, multiple regression analysis, path analysis, factor and  canonical covariate analysis. Almost every year, within a cohort of last 53 years, coastal agriculture of Odisha has  experienced brunt of 40 years of drought, flood or cyclones. This has been reflected in the stagnating yield of food crops  over the couple of decades, negating the positive impact of modern technology and fertilizer application in the operating  farms. The result shows that, the variables like, age (X1), education (X2) & changing expenditure allocation on education  (X10), change pattern of watching television, listening to radio, all have been redeemed into a dependable estimator of  perception on climate change effect on agriculture.
Keywords: Climate change; coastal agriculture; perception